Identifying the needs for competency-based education in Europe: a needs assessment of cardiologists across 52 countries. Issue 1 (1st January 2017) - Murray, S.; Carrera, C.; Lazure, P.; Vardas, P.; Zamorano, J. L.; Kearney, P.; Goncalves, L.; Fox, K.; Vahanian, A.
ABSTRACT: Objective : This international needs assessment was mandated by the European Society of Cardiology (ESC) to obtain an in-depth understanding of the current gaps and challenges of European cardiology professionals, with the aim to provide evidence for the development of needs-driven educational and professional development activities. Methods : This ethics-approved needs assessment was conducted among cardiologists from all sub-specialties across 56 countries of Europe and the Mediterranean basin. A mixed-methods research approach was used, combining qualitative in-depth interviews and focus groups with a quantitative survey. Results : Seventy-four (74) cardiologists participated in the qualitative phase and 866 completed the survey. Respondents represented 52 of the 56 targeted countries. Three themes were identified: 1) Challenges in the clinical decision-making process, 2) Challenges in establishing the patient-physician relationship, and 3) Sub-optimal team communication and collaboration. Specific gaps and causalities related to each challenge were found. Although most of the gaps were common across countries and sub-specialties, some significant differences were noted. Conclusion : The findings of this needs assessment indicate gaps and challenges in clinical practice across countries and across sub-specialities. Taking cardiology as an example, this study identifies clear areas of focus, especially around issues of collaboration and communication, for targeted competency-based education in Europe.